Cross continental increase in methane ebullition under climate change - Ralf C. H. Aben; Nathan Barros; Ellen van Donk; Thijs Frenken; Sabine Hilt; Garabet Kazanjian; Leon P. M. Lamers; Edwin T. H. M. Peeters; Jan G. M. Roelofs; Lisette N. de Senerpont Domis; Susanne Stephan; Mandy Velthuis; et al. (Nature Communications, 2017)
The impacts of climate change on natural methane (CH4) emissions via ebullition are unclear. Here, using published and experimental multi-seasonal CH4 ebullition data, the authors find a strong relationship between CH4 ebullition and temperature across a wide range of freshwater ecosystems globally.